Temperature-fluctuation effects on shrimp protein quality assessed via a multi-stage temperature-fluctuation protein convolutional neural network - Zhexun Yang; Yiling Zhang; Sili Xiao; Weiteng Weng; Ziqi Xie; Jiayi Li; Wen Jie Li; Ying Deng; Yutao Wei; Yudan Li; Shuangyin Liu; Xuekai Gao; et al. (Journal of Food Engineering, 2027)

Molecular interactions between curcumin and diverse-source type Ⅰ/II gelatins: Complex fabrication and utilization in pickering emulsion systems - Zhexun Yang; Ziqi Xie; Sili Xiao; Yiling Zhang; Weidong Bai; Qiaoyu Liu (Food Hydrocolloids, 2026)

Degradation tag-regulated transcription factor toolkit for graded gene expression and enhanced biosynthesis in Halomonas bluephagenesis - Shimao Yang; Xiaofan Jin; Hongtao He; Xinyu Chen; Mingwei Shao; Yiling Chen; Fuqing Wu; Fang Yang; Guo-Qiang Chen (Chemical Engineering Journal, 2026)

Novel oxygen vacancy modified CuBi2O4/FeWO4 S-scheme heterojunction for efficient peroxymonosulfate activation toward antibiotics degradation - Wenhao Zhu; Yiling Cui; Tongxiang Liang; Jinming Zeng; Qingqing Qiu; Kai Yang (Chemical Engineering Journal, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

Z-scheme Cd0.5Zn0.5S/FeWO4 heterojunction with oxygen vacancies for tetracycline hydrochloride degradation: Mechanisms insight and DFT calculations - Kailin Chen; Wenhao Zhu; Yiling Cui; Ao Fan; Qingqing Qiu; Kai Yang; Jinming Zeng; Tongxiang Liang (Journal of Environmental Chemical Engineering, 2026)

The impacts of multidimensional urban greenness on incident dyslipidaemia and blood lipid profiles among adults: A 10-year longitudinal cohort study in Hong Kong - Yufei Liu; Siyi Chen; Changqing Lin; Yiling Zheng; Yuanyuan Yi; Jun Yang; Shiu Lun Au Yeung; Jun Ma; Weifeng Li; Tuan Quang Phan; Lingxin Hao; Cui Guo (Environmental Research, 2026)

Synergistic catalytic elimination of NOx and chlorobenzene over Mn₅Ce₃/TiO₂/ZSM-5 catalyst: Insight into the performance and mechanism under C3H6-SCR conditions - Bo Yang; Yiling He; Yujie Lei; Qiong Huang; Mindong Chen (Journal of Environmental Chemical Engineering, 2026)

Modulation of the rhizosphere microbial network by dark septate endophytes enhances salt tolerance in Lycium ruthenicum Murr - Han Li; Meng Zhou; Zhengyu Zhu; Mengmeng Li; Xiaotong Yang; Yiling Zuo; Xueli He (International Biodeterioration & Biodegradation, 2026)

On-site evolution of bifunctional NiCoP nanosheet electrode for electrocatalytic co-produce acetate and hydrogen from ethanol - Nanjia Yang; Yongsheng Wang; Yanan Chen; Yizhen Li; Jiansheng Wang; Chuanyi Zhang; Kaifeng Wang; Yiling Feng; Yuxin Zhu; Wei Zhu; Zhongbin Zhuang (Chemical Engineering Journal, 2026)

Efficient and stable membrane fouling control in MFC-MBR system facilitated by conductive membrane electrodes - Xiao Zhu; Yiling Gu; Nan Jiang; Jiaping Wu; Wenxin Chen; Suhao Feng; Ding Huang; Jianmao Yang; Manhong Huang (Journal of Water Process Engineering, 2026)

Oligomer production and effects on gut microbiota of PLA and PBAT biodegradable microplastics in in vitro digestion model - Guowei Ma; Xiaomeng Gao; Zhihui Li; Yuting Chen; Hanfei Li; Yiling Cui; Peixue Guo; Biao Yang; Di Feng; Tingting Zhao (Food Bioscience, 2026)

Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

Toward a comprehensive map of Rab-mediated cargo transport to migrasomes - Yiling Wen; Yong Li; Jiayi Chen; Dianxing Liu; Yuanchao Li; Ying Li; Haohao Tang; Peizhen Gao; Wenmin Tian; Ning Shen; Yang Chen (Science China Life Sciences, 2026)

Leaching behavior and toxicity of solid waste from ore-based lithium extraction: Implications for safe storage and resource utilization - Jiefeng Liang; Luqian Zheng; Qun Zhang; Jiawen Yang; Bo Lei; Feigang Yuan; Mingyang Li; Wei Jiang; Yiling Li; Xuezhi Yang; Runzeng Liu; Haiyan Zhang; et al. (Water Research, 2026)

Migrion: a Migrasome-mediated unit for intercellular viral transmission - Yuxing Huang; Xiaojie Yan; Xing Liu; Congcong Ji; Wenmin Tian; Haohao Tang; Yong Li; Yiling Wen; Peiyao Fan; Hongli Wang; Cankun Xi; Zhongtian Li; et al. (Science Bulletin, 2026)

Hematotoxicity of Fe- and Cr-based metal–organic framework nanoparticles in rockfish Sebastes schlegelii - Yiling Li; Junyu Ye; Meiyu Wang; Yang Gao; Bin Xia; Zhengguo Cui; Keming Qu (Marine Environmental Research, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

Enhancing agroforestry system resilience: Harnessing environmental vulnerability data to map restoration and pave the way for karst desertification control - Jie Xiao; Yiling Yang; Kangning Xiong; Shilian Jiang; Yunting Huang (Agricultural Systems, 2026)

Constructing a macroporous N-doped carbon hosted ZnO/Fe3O4 composite from Fe-ZIF-8 pyrolysis for highly sensitive detection of carbendazim environmental pollutants - Yaqi Yang; Jiejun Li; Yiling Wang; Zhifang Liu; Caiyu Ge; Yixi Xie; Pengcheng Zhao; Junjie Fei (Journal of Environmental Chemical Engineering, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Tannic acid: A star molecule in the construction and biomedical applications of hydrogels - Wei Zhang; Yiling Chen; Jing Huang; Ziyi Xiao; Fangjing Wang; Guihui Zhu; Xinying Liao; Yuxin Tang; Zhihao Song; Jian Sun; Yang Liu (Chemical Engineering Journal, 2025)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

Spatiotemporal dependence of heavy precipitation on soil moisture anomalies in the Yangtze River Basin, China - Na Yang; Yiling Yue; Hang Yu; Li Zhang; Jun Yin; Junjie Gao; Yehui Zhang (Science of The Total Environment, 2025)

Production and characterization of copolymers consisting of 3-hydroxybutyrate and adjustable lactate by engineered Halomonas bluephagenesis from glucose - Jiangnan Chen; Fang Yang; Xinyu Chen; Yiling Chen; Zhenghao Xu; Shi Mu; Guo-Qiang Chen (Bioresource Technology, 2025)

Evaluation and optimization of a cascade PEMFC system for enhancing coalbed methane recovery considering carbon capture and carbon taxes - Aixiang Xu; Qi Yang; Lanxiang Yang; Wei Huang; Yiling Ke; Zihao Wang; Sheng Yang; Chengwei Deng (Process Safety and Environmental Protection, 2025)

A new framework for evaluating land suitability for Goji (Lycium barbarum L.) cultivation across China - Yunpeng Hong; Yiling Chen; Yanyan Su; Gangqiang Dong; Xiaodong Song; Jing Zhang; Han Wang; Zhongxiu Sun; Long Guo; Jinling Yang; Ganlin Zhang (Journal of Environmental Management, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

Biosynthesis of poly(δ-valerolactone) (PVL) by Halomonas bluephagenesis - Jiale Wang; Xu Yan; Shuang Zheng; Rou Wen; Yiling Chen; Weinan Yang; Junting Sheng; Qiong Wu; Fuqing Wu; Guo-Qiang Chen (Chemical Engineering Journal, 2025)

Curcumin activates the JAK-STAT signaling pathway to enhance the innate immune response against porcine epidemic diarrhea virus infection in vivo and in vitro - Qiancheng Jiang; Xiangyang Liu; Jianbo Yuan; Shujuan Zhang; Yiling Zhang; Zifei Kan; Zheng Niu; Li Zhang; Xia Hu; Yang Zhou; Jing Wang; Fei Li; et al. (Veterinary Microbiology, 2025)

DSE enhances fungal modularity and bacterial connectivity linking rhizospheric responses to licorice growth and drought resistance - Yiling Zuo; Chao He; Xinrong Yang; Wanyun Li; Xueli He (Rhizosphere, 2025)

Dielectric behavior of frozen dough during thawing: Insights into phase transition, mobility, and migration of water - Yiling Yang; Yuan Tao; Yejun Wu; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2025)

Understanding how agroforestry systems biodiversity drives ecosystem services in degraded habitats - Yiling Yang; Jie Xiao; Yunting Huang; Shilian Jiang (Journal of Environmental Management, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Polyhydroxyalkanoate production by engineered Halomonas grown in lignocellulose hydrolysate - Yiping Yuan; Huan Wang; Hongtao He; Zhongnan Zhang; Fang Yang; Yiling Chen; Fuqing Wu; Qiong Wu; Guo-Qiang Chen (Bioresource Technology, 2025)

Homozygous deleterious variants in MYCBPAP induce asthenoteratozoospermia involving abnormal acrosome biogenesis, manchette structure and sperm tail assembly in humans and mice - Yiling Zhou; Chaofeng Tu; Charles Coutton; Jianan Tang; Shixiong Tian; Shuyan Tang; Guillaume Martinez; Dapeng Zhou; Célia Tebbakh; Jiaxiong Wang; Raoudha Zouari; Xuehai Zhou; et al. (Science China Life Sciences, 2025)

Vetch cover crops increase particulate organic carbon in citrus orchard by increasing lignin phenols - Jiajia Zhang; Lei Lei; Wenfa Xiao; Xin Yang; Willam R. Horwath; Yiling Liao; Hongbing Yang; Zunji Jian; Lixiong Zeng (Applied Soil Ecology, 2025)

HTBPPS: A high-throughput behavioral phenotyping platform for shrimp - Wenzhi Cheng; Huimin Peng; Chuanxi Chen; Heqian Zhang; Yiming Wei; Jinqian Yang; Xiaojie Deng; Yiling Hou; Siqi Li; Tingting Huang; Yougen Chen; Chichi Liu; et al. (Aquaculture, 2025)

Disruption of network hierarchy pattern in bulimia nervosa reveals brain information integration disorder - Yiling Wang; Lirong Tang; Jiani Wang; Weihua Li; Miao Wang; Qian Chen; Zhenghan Yang; Zhanjiang Li; Zhenchang Wang; Guowei Wu; Peng Zhang (Appetite, 2024)

Efficient activation of peracetic acid by defect-engineered MoO2−x: Oxygen vacancies and surface Mo(Ⅴ)-mediated electron transfer processes - Jinpeng Wang; Boran Wang; Yubiao Li; Yiling Yang; Caiyan Gao; Xiaoyong Wu (Journal of Hazardous Materials, 2024)

Niche-specific evolution and gene exchange of Salmonella in retail pork and chicken - Huanjing Sheng; Linna Zhao; Jia Suo; Qiuping Yang; Chenyang Cao; Jia Chen; Guangqing Cui; Yiling Fan; Yi Ma; Shengnan Huo; Xin Wu; Tao Yang; et al. (Food Research International, 2024)

Effect of psychrotrophic Lactiplantibacillus plantarum L75 with exoploysaccharides-producing property on fermentation, bacterial community, and antioxidant activity of oat silage at low temperature - Rina Su; Xinyuan Cui; Hao Guan; Wencan Ke; Ying Liang; Hu Chen; Neha Sheoran; Mengya Jia; Yiling Yang; Lizhuang Hao; Guojun Zhao; Xusheng Guo (Animal Feed Science and Technology, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Numerical investigation on the influence of CO2-induced mineral dissolution on hydrogeological and mechanical properties of sandstone using coupled lattice Boltzmann and finite element model - Bo Yang; Tianfu Xu; Yiling Du; Zhenjiao Jiang; Hailong Tian; Yilong Yuan; Huixing Zhu (Journal of Hydrology, 2024)

LC–MS and MALDI–MSI-based metabolomic approaches provide insights into the spatial–temporal metabolite profiles of Tartary buckwheat achene development - Tingxia Liu; Peng Wang; Yiling Chen; Boshi Sun; Qing Li; Huihua Wan; Wei Yang; Pengda Ma; Dong Zhang; Gangqiang Dong; Shilin Chen; Qingfu Chen; et al. (Food Chemistry, 2024)

Two cytokine receptor family B (CRFB) members in orange-spotted grouper Epinephelus coioides, EcCRFB3 and EcCRFB4, negatively regulate interferon immune responses to assist nervous necrosis virus replication - Siyou Huang; Yiling Kang; Rui Zheng; Linwei Yang; Jie Gao; Wanting Tang; Jing Jiang; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Correction to: Structure-activity relationships and pharmacokinetic evaluation of L-cystine diamides as L-cystine crystallization inhibitors for cystinuria - Longqin Hu; Haifa Albanyan; Jeffrey Yang; Xiangduan Tan; Yiling Wang; Min Yang; Xiaodi Zhong; Michael D. Ward; Amrik Sahota (Medicinal Chemistry Research, 2024)

Structure-activity relationships and pharmacokinetic evaluation of L-cystine diamides as L-cystine crystallization inhibitors for cystinuria - Longqin Hu; Haifa Albanyan; Jeffrey Yang; Xiangduan Tan; Yiling Wang; Min Yang; Xiaodi Zhong; Michael D. Ward; Amrik Sahota (Medicinal Chemistry Research, 2024)
Cystinuria is a rare genetic disorder characterized by defective l -cystine reabsorption from the renal proximal tubule, resulting in abnormally high concentrations of L-cystine and subsequent l -cystine crystallization and stone formation in urine. l -Cystine diamides have shown great promise as inhibitors of l -cystine crystallization. The free α-amino groups in l -cystine diamides have previously been shown to be necessary for l -cystine crystallization inhibitory activity. In this study, three additional series of l -cystine diamide analogs were designed to explore further the structure-activity relationships for l -cystine crystallization inhibition. It has been demonstrated that the middle disulfide bond is required for optimal l -cystine crystallization inhibitory activity, and the only regions that can be modified are the two terminal amides. The presence of another basic amine 2–3 atoms away from the amide nitrogen is also critical for optimal activity. Disulfide exchange was found to be the main metabolic pathway resulting in the formation of two molecules of the active mixed disulfide metabolite from a single l -cystine diamide. l -Cystine diamides have the potential to be developed into a much-needed therapy for cystinuria.

Rapid fluorescent nucleic acid sensing with ultra-thin gold nanosheets - Peiyin Li; Huiyang Zhang; Zhenyu Yang; Yiling Li; Manli Huang; Lingzhi Yang; Xueji Zhang (Analytica Chimica Acta, 2024)

A Comprehensive Analysis of NRP1 in Malignancies Provide Therapeutic Implication for Treating Cancer Patients Infected with SARS-CoV-2 - Shuzhao Chen; Limei Zhang; Yiling Song; Kunying Xie; Yun Wang; Yang Liang (Biochemical Genetics, 2024)

A review of agroforestry biodiversity-driven provision of ecosystem services and implications for karst desertification control - Yiling Yang; Kangning Xiong; Jie Xiao (Ecosystem Services, 2024)

Inhalation exposure to polystyrene nanoplastics induces chronic obstructive pulmonary disease-like lung injury in mice through multi-dimensional assessment - Sheng Yang; Tianyi Zhang; Yiling Ge; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Pollution, 2024)

LDH nanocrystal@amorphousness core–shell structure derived from LDH → LDO transformation: Synergistically enhanced energy stored for LIBs anode - Kai Yang; Yiling Huang; Peixing Wang; Yixuan Tang; Yiwen Zhu; Xiaoxue Zhu; Yan Xu; Wei Jiang; Limei Pan; Qian Li; Haijiao Xie; Jian Yang (Chemical Engineering Journal, 2024)

Ferroptosis participated in inhaled polystyrene nanoplastics-induced liver injury and fibrosis - Yiling Ge; Sheng Yang; Tianyi Zhang; Saisai Gong; Xin Wan; Yuxin Zhu; Yifei Fang; Chengyu Hu; Fei Yang; Lihong Yin; Yuepu Pu; Zaozao Chen; et al. (Science of The Total Environment, 2024)

Photocatalytic activation of oxalic acid over FeOOH loaded FeWO4/WO3 heterojunction for high-efficient degradation of tetracycline - Qingqing Chai; Jiahan Dong; Xiaofang Yu; Xiaoke Zhang; Jun Li; Sheng Guo; Yiling Yang (Journal of Environmental Chemical Engineering, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

A near-infrared emitting “off-on” fluorescent probe for bioimaging of Pd(Ⅱ) ions in living cells and mice - Xiao-Fei Chen; Yu Song; Yiling Liu; Yang Zhou; Xin Zhao; Zifeng Yang (Analytica Chimica Acta, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Chiral Au nanostars for SERS sensing of enantiomers discrimination, multibacteria recognition and photothermal antibacterial application - Xueqin Huang; Qiuxia Chen; Yiling Ma; Chan Huang; Weixia Zhi; Jiahao Li; Runmin Zeng; Jiang Pi; Jun-fa Xu; Jun Xu; Wanyong Yang; Jianglin Zhang; et al. (Chemical Engineering Journal, 2024)

The hepatotoxicity assessment of micro/nanoplastics: A preliminary study to apply the adverse outcome pathways - Yiling Ge; Sheng Yang; Tianyi Zhang; Xin Wan; Yuxin Zhu; Fei Yang; Lihong Yin; Yuepu Pu; Geyu Liang (Science of The Total Environment, 2023)

Effect of cooking methods on metabolites of deep purple-fleshed sweetpotato - Xia Jiang; Rong Zhang; Yanqiang Yao; Yiling Yang; Bin Wang; Zhangying Wang (Food Chemistry, 2023)

Research advances of molecular docking and molecular dynamic simulation in recognizing interaction between muscle proteins and exogenous additives - Genpeng Bai; Yiling Pan; Yuemei Zhang; Yang Li; Jinpeng Wang; Ying Wang; Wendi Teng; Guofeng Jin; Fang Geng; Jinxuan Cao (Food Chemistry, 2023)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

Amine-functionalized cotton for the treatment of oily wastewater - Yiling Ao; Ji'an He; Keming Chen; Mingzhao Zhu; Fan Ye; Liwei Shen; Ying Yang; Xuening Feng; Zejun Zhang; Yuqi Tang; Yuanzhu Mi (Environmental Research, 2023)

Understanding post-pandemic metro commuting ridership by considering the built environment: A quasi-natural experiment in Wuhan, China - Hong Yang; Yi Lu; Jingjing Wang; Yiling Zheng; Zehan Ruan; Jiandong Peng (Sustainable Cities and Society, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

Analysis of influencing factors and prediction of China’s Containerized Freight Index - Xiaoying Tu; Yiling Yang; Yu Lin; Shiqun Ma (Frontiers in Marine Science, 2023)
China, as a major maritime nation, the China Containerized Freight Index (CCFI) serves as an objective reflection of the Chinese shipping market and an important indicator for understanding China’s shipping industry globally. The shipping market is a complex ecosystem influenced by various factors, including vessel supply and demand, cargo supply and demand relationships and prices, fuel prices, and competition from substitute and complementary markets. To analyze and study the state of the Chinese shipping market, we selected the CCFI as an indicator and collected data on six factors that may affect the overall shipping market. These factors include “ the China Coastal Bulk Freight Index(CCBFI)”, “the Baltic Dry Index(BDI)”, “the Yangtze River Container Freight Index”, “Global: Aluminum (minimum purity of 99.5%, London Metal Exchange (LME) spot price): UK landed price”, “Major Ports: Container Throughput”, and “Coal Price: US Central Appalachia: Coal Spot Price Index”. Then, we constructed an analyticaland predictive framework using Deep Neural Network (DNN), CatBoost regression model, and robust regression model to study the CCFI. Based on the R 2 results of the three models, it is evident that DNN provides the best analytical and predictive performance for the CCFI, accurately forecasting its changes. Additionally, the robust regression model indicates that “Global: Aluminum (minimum purity of 99.5%, LME spot price): UK landed price” has the greatest impact on the CCFI. Finally, from a business perspective, we provide some suggestions for China’s container shipping industry.

Development of an LC-MS/MS method for the determination of multiple mycotoxins in human urine - Mobing Chen; Wei Liu; Ping Xiang; Linhao Xu; Yiling Tang; Ran Kong; Shuo Yang; Hui Yan; Bin Di (Food Additives & Contaminants: Part A, 2023)

Effects of dietary adenosine and adenosine 5′-monophosphate supplementation on carcass characteristics, meat quality, and lipid metabolism in adipose tissues of finishing pigs - Sujuan Rao; Zhijuan Cui; Longmiao Zhang; Shuo Ma; Shuangbo Huang; Li Feng; Yiling Chen; Jinxi Luo; Jinfeng Li; Shiyu Qian; Hanting Liu; Yanzhi Liu; et al. (Meat Science, 2023)

A smartphone-assisted “all-in-one” paper chip for one-pot noninvasive detection of salivary glucose level - Qian Lin; Jiaqi Huang; Yiling Zhang; Miaomiao Chen; Yuzhi Xu; Xiaoyong Zou; Si-Yang Liu; Zong Dai (Chemical Engineering Journal, 2023)

Development of convenient crystallization inhibition assays for structure-activity relationship studies in the discovery of crystallization inhibitors - Jeffrey Yang; Haifa Albanyan; Yiling Wang; Yanhui Yang; Amrik Sahota; Longqin Hu (Medicinal Chemistry Research, 2023)

Bone marrow mesenchymal stem cell-derived exosomes loaded with miR-26a through the novel immunomodulatory peptide DP7-C can promote osteogenesis - Shuang Lai; Li Deng; Cong Liu; Xinlun Li; Liyuan Fan; Yushu Zhu; Yiling Yang; Yandong Mu (Biotechnology Letters, 2023)

Understanding the ecological effects of the fungicide difenoconazole on soil and Enchytraeus crypticus gut microbiome - Guoyan Qin; Qi Zhang; Ziyao Zhang; Yiling Chen; Jichao Zhu; Yaohui Yang; W.J.G.M. Peijnenburg; Haifeng Qian (Environmental Pollution, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

A chromosome‐level Populus qiongdaoensis genome assembly provides insights into tropical adaptation and a cryptic turnover of sex determination - Yiling Li; Deyan Wang; Weiwei Wang; Wenlu Yang; Jinwen Gao; Wenyan Zhang; Lanxing Shan; Minghui Kang; Yang Chen; Tao Ma (Molecular Ecology, 2023)
Populus species have long been used as model organisms to study the adaptability of trees and the evolution of sex chromosomes. As a species belonging to the section Populus and limited to tropical areas, the P. qiongdaoensis genome contains important information for tropical poplar studies and protection. Here, we report a chromosome‐level genome assembly and annotation of a female P. qiongdaoensis . Gene family clustering, positive selection detection and historical reconstruction of population dynamics revealed the tropical adaptation of P. qiongdaoensis , and showed convergent evolution with another tropical poplar, P. ilicifolia , at the molecular level, especially on some functional genes (e.g., PIF3 and PIL1 ). In addition, we also identified a ZW sex determination system on chromosome 19 of P. qiongdaoensis , and inferred that it seems to have a similar sex determination mechanism to other poplars, controlled by a type‐A cytokinin response regulator ( RR ) gene. However, comparison and phylogenetic analysis of the sex determination regions confirmed a cryptic sex turnover event in the section Populus , which may be caused by the translocation and duplication of the RR gene driven by Helitron ‐like transposable elements. Our study provides new insights into the environmental adaptation and sex chromosome evolution of poplars, and emphasizes the importance of using long read sequencing in ecological and evolutionary inferences of plants.

The capability of chloramphenicol biotransformation of Klebsiella sp. YB1 under cadmium stress and its genome analysis - Zewen Tan; Xiuyue Yang; Yiling Liu; Lian Chen; Huijuan Xu; Yongtao Li; Beini Gong (Chemosphere, 2023)

Pollution mechanisms and photochemical effects of atmospheric HCHO in a coastal city of southeast China - Taotao Liu; Yiling Lin; Jinsheng Chen; Gaojie Chen; Chen Yang; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Youwei Hong (Science of The Total Environment, 2023)

Challenging the limits of the oxygen balance of a pyrazole ring - Wenjin Zhang; Yiling Yang; Yuchuan Wang; Teng Fei; Yu Wang; Chenghui Sun; Siping Pang (Chemical Engineering Journal, 2023)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Exploration of molecular mechanism of intraspecific cross-incompatibility in sweetpotato by transcriptome and metabolome analysis - Yiling Yang; Xiongjian Zhang; Hongda Zou; Jingyi Chen; Zhangying Wang; Zhongxia Luo; Zhufang Yao; Boping Fang; Lifei Huang (Plant Molecular Biology, 2022)
Cross-incompatibility, frequently happening in intraspecific varieties, has seriously restricted sweetpotato breeding. However, the mechanism of sweetpotato intraspecific cross-incompatibility (ICI) remains largely unexplored, especially for molecular mechanism. Treatment by inducible reagent developed by our lab provides a method to generate material for mechanism study, which could promote incompatible pollen germination and tube growth in the ICI group. Based on the differential phenotypes between treated and untreated samples, transcriptome and metabolome were employed to explore the molecular mechanism of sweetpotato ICI in this study, taking varieties ‘Guangshu 146’ and ‘Shangshu 19’, a typical incompatible combination, as materials. The results from transcriptome analysis showed oxidation–reduction, cell wall metabolism, plant–pathogen interaction, and plant hormone signal transduction were the essential pathways for sweetpotato ICI regulation. The differentially expressed genes (DEGs) enriched in these pathways were the important candidate genes to response ICI. Metabolome analysis showed that multiple differential metabolites (DMs) involved oxidation–reduction were identified. The most significant DM identified in comparison between compatible and incompatible samples was vitexin-2-O-glucoside, a flavonoid metabolite. Corresponding to it, cytochrome P450s were the most DEGs identified in oxidation–reduction, which were implicated in flavonoid biosynthesis. It further suggested oxidation–reduction play an important role in sweetpotato ICI regulation. To validate function of oxidation–reduction, reactive oxygen species (ROS) was detected in compatible and incompatible samples. The green fluorescence was observed in incompatible but not in compatible samples. It indicated ROS regulated by oxidation–reduction is important pathway to response sweetpotato ICI. The results in this study would provide valuable insights into molecular mechanisms for sweetpotato ICI.

Growth-promoting effects of dark septate endophytes on the non-mycorrhizal plant Isatis indigotica under different water conditions - Min Li; Lifeng Hou; Jiaqiang Liu; Jingya Yang; Yiling Zuo; Lili Zhao; Xueli He (Symbiosis, 2021)

Overexpression of MeDREB1D confers tolerance to both drought and cold stresses in transgenic Arabidopsis - Yiling Yang; Wenbin Liao; Xiaoling Yu; Bin Wang; Ming Peng; Mengbin Ruan (Acta Physiologiae Plantarum, 2016)

Functional response of the fungus Hirsutella rhossiliensis to the nematode, Heterodera glycines - Chi Shu; YiLing Lai; EnCe Yang; SenYu Chen; MeiChun Xiang; XingZhong Liu (Science China Life Sciences, 2015)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

Characterization of Pseudomonas corrugata Strain P94 Isolated from Soil in Beijing as a Potential Biocontrol Agent - Yanbin Guo; Hui Zheng; Yiling Yang; Huimin Wang (Current Microbiology, 2007)